Reasons and Pattern of Teeth Extraction in a Maxillofacial Clinic in Northern Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Exodontia or teeth extraction make up the majority of workload in the minor surgery of most oral and maxillofacial surgery clinics in our environment. Extraction of teeth represents different percentages amongst children and adult populations and private and public clinics, respectively, also.Aims:The aim of this study was to determine the indications for and pattern of teeth extraction in patients presenting at the maxillofacial surgery clinic.Settings and Design:Records of patients who had teeth extractions at the Oral and Maxillofacial Surgery Clinic between 1st January 2006 and 31stDecember 2018 were retrieved and retrospectively studied from the Medical Records and the Minor Surgery register book.Methods and Materials:The biodata and indications for extraction were recorded.Results:A total of 1220 records from the year 2006 to 2018 were used to conduct the research. They comprised 636 (52.1%) males and 584 (47.9%) females. Their age range was 2 years to 92 years with a mean age of 31.8 ± 14.6. The most predominant age group that attended clinic for extraction was the 20–29 years of age accounting for 35.6% of the study participants with more males 228 (52.3) than the females 208 (47.7).Conclusion:Dental caries and its sequelae continue to be the leading cause of tooth extraction in our environment, followed by tooth impaction as well as pericoronitis around impacted teeth.